THE EXISTENCE OF HEART IN HADITH REVIEW - Assagaf, M. Yusuf; Ilyas, Abustani; Tangngareng, Tasmin; Ahmad, La Ode Ismail (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This paper discussed hadith related to the existence of the heart with main topics 1) the quality of the hadith and 2) content. The results of this study indicate that the existence of heart hadith based on the transmission consists of 16 lines (sanad) which are spread in the book of 9 imams (al-kutub al-tis'ah) and narrated in meaning. In addition, 1) the existence of heart hadith has good quality, both in terms of the sanad and matan, and 2) the hadith shows the existence of the heart as a treasury of abstract issues, such as; beliefs, feelings, disbelief, and others. In addition, the liver is an organ that plays a role in giving a command to all body organs to move. This paper is expected to understand the broader community that the heart has a vital role in the excellent condition of the body and human actions, especially to achieve the best level as human beings mentioned in QS al-Hujurat(49:13).